2022
DOI: 10.1155/2022/1411371
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Effect of Continuous Blood Purification Combined with Humanized Nursing in Patients with Severe Sepsis

Abstract: This work aimed to explore the effect of humanized nursing on the patients’ recovery from severe sepsis based on continuous blood purification (CBP). 90 patients with severe sepsis were randomly and equally divided into a control group (basic intensive nursing + CBP) and a therapy group (humanized nursing + CBP). Before treatment and on the 7th and 14th days after treatment, indicators of patients were compared, including white blood cell (WBC), tumor necrosis factor (TNF-α), hepatic and renal function, C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%